A Review of How Lasers Are Used in UTUC Surgery: Can the Choice of Laser Affect Outcomes? - Taratkin, Mark; Singla, Nirmish; Babaevskaya, Diana; Androsov, Alexander; Shariat, Shahrokh F; Fajkovic, Harun; Baniel, Jack; Enikeev, Dmitry (Cancers, 2023)
Upper tract urothelial carcinoma (UTUC) is a relatively rare disease with an aggressive phenotype compared to urothelial carcinoma in the bladder. In recent years, kidney-sparing surgery (KSS) and, in particular, endoscopic surgery have become the procedure of choice among urologists where the treatment of localized UTUC is concerned. Endoscopy tends to result in satisfactory oncological disease control while lowering morbidity and minimizing complications amongst the appropriately selected cohort of patients. While endoscopic surgery for UTUC might appear to be standardized, it, in fact, differs considerably depending on the source of energy used for resection/ablation. There has been little reliable data up to now on which laser energy source is the most superior. The goal of this review is, therefore, to outline the results of endoscopic UTUC treatment using different lasers and to analyze how these laser-tissue interactions may affect the surgery. We start by pointing out that the data remains insufficient when trying to determine which laser is the most effective in the endoscopic management of UTUC. The ever-growing number of indications for minimally invasive treatment and the increasing number of centers using laser surgery will, hopefully, lead to novel randomized controlled trials that compare the performance characteristics of the lasers as well as the effects of UTUC on patients.
Keywords: laser ablation; upper tract urothelial cell carcinoma (UTUC); endoscopic treatment; kidney-sparing surgery